Implicative Almost Distributive Lattice - Berhanu Assaye Alaba; Mihret Alamneh; Tilahun Mekonnen Munie ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2018)
In this paper, we introduce the concept of Implicative Almost Distributive Lattices (IADLs) as a generalization of implicative algebra in the class of Almost Distributive Lattices. We discuss some properties of IADL and derive some equivalent conditions in IADLs. We also discuss some characterizations of IADL to become an implicative algebra